Preparation method of piezoelectric nanofiber flexible composite film with 3D conductive network
By growing CNTs on piezoelectric nanofiber membranes and forming a 3D conductive network, the problem of building conductive paths in tight piezoelectric nanofiber membranes is solved, and the output performance of piezoelectric nanogenerators is significantly improved.
Patent Information
- Application Number
- CN202411979831.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art is difficult to construct well-distributed conductive paths in regular arrangement and dense piezoelectric nanofiber membranes, which limits the output performance of piezoelectric nanogenerators.
Directedly arranged nanofiber membranes were prepared by electrospinning technology, and carbon nanotubes (CNTs) were grown in situ by chemical vapor deposition to form a 3D conductive network that synergistically interacted by conductive nanofibers and CNTs.
The built 3D conductive network improves charge density and piezoelectric output performance, solves the problem of conductive path construction, and improves the performance of flexible piezoelectric nanogenerators.
Smart Images

Figure CN119789765A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of piezoelectric materials, and in particular to a method for preparing a piezoelectric nanofiber flexible composite film having a 3D conductive network (ie, a three-dimensional conductive network). Background Art
[0002] Piezoelectric nanogenerator (PENG) is an electronic device that can convert mechanical vibration into electrical energy for the supply of sustainable energy. Considering the potential applications of PENG in energy harvesting, health diagnosis, motion monitoring, etc., PENG must have good flexibility to cope with complex strains such as bending, stretching and torsion. However, most materials with high piezoelectric coefficients are hard and brittle ceramic materials, which limits their further development. To overcome this defect, embedding piezoelectric ceramics in flexible polymers to construct organic / inorganic composite flexible PENG is a feasible solution. However, the polymer present in the gap isolates the piezoelectric ceramics and limits the piezoelectric charge transfer, which seriously affects the piezoelectric output performance of PENG.
[0003] In order to solve the above problems, an effective method is to use conductive materials to construct conductive paths between piezoelectric materials to enhance the transmission of piezoelectric charges, thereby enhancing the piezoelectric output performance of PENG. In 2012, Park et al. first proposed a strategy of adding multi-walled carbon nanotubes (MWCNTs) to flexible polydimethylsiloxane / barium titanate (PDMS / BaTiO3) composites to improve their piezoelectric properties, where MWCNTs can form conductive paths, thereby improving output performance. Based on the above research, it can be seen that conductive paths play an important role in charge transfer in organic / inorganic composite flexible PENGs.
[0004] Although high-performance PENG can be obtained by introducing conductive pathways into organic / inorganic composite piezoelectric materials to improve the charge transfer capability, it is extremely challenging to construct well-distributed conductive pathways in the orderly and dense piezoelectric nanofibers using conductive materials such as CNTs and metal nanoparticles. Summary of the invention
[0005] In view of the deficiencies in the prior art, the technical problem that the present invention intends to solve is to provide a method for preparing a piezoelectric nanofiber flexible composite membrane with a 3D conductive network.
[0006] The technical solution of the present invention to solve the technical problem is to provide a method for preparing a piezoelectric nanofiber flexible composite film with a 3D conductive network, characterized in that the method comprises the following steps: (1) Preparation of piezoelectric / conductive nanofiber membrane: preparing a piezoelectric material precursor electrospinning solution and a conductive material precursor electrospinning solution, and then using the two spinning solutions as raw materials, placing them in two syringes of an electrospinning device for electrospinning to form a piezoelectric / conductive precursor nanofiber membrane; wherein all the precursor nanofibers in the piezoelectric / conductive precursor nanofiber membrane are arranged along the rotation direction of a collecting device of the electrospinning device; and then calcining the piezoelectric / conductive precursor nanofiber membrane to decompose the polymer carrier in the membrane to obtain a piezoelectric / conductive nanofiber membrane; (2) Preparation of CNT@piezoelectric / conductive nanofiber membrane: CNTs are grown in situ on the piezoelectric / conductive nanofiber membrane by chemical vapor deposition to obtain CNT@piezoelectric / conductive nanofiber membrane; (3) Preparation of CNT@piezoelectric / conductive nanofiber / PDMS composite membrane: Several CNT@piezoelectric / conductive nanofiber membranes are stacked layer by layer to form a three-dimensional structure, and the arrangement direction of the nanofibers in each layer of CNT@piezoelectric / conductive nanofiber membrane is the same; then they are immersed in a PDMS solution and allowed to stand, so that the PDMS adheres to the inside and surface of the nanofiber membrane; then a curing treatment is performed to solidify the PDMS, and then the three-dimensional structure is cut along the radial direction of the nanofibers in the three-dimensional structure to obtain a CNT@piezoelectric / conductive nanofiber / PDMS composite membrane.
[0007] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses electrospinning technology to prepare directional nanofibers, and the conductive nanofibers and piezoelectric nanofibers are evenly mixed. Then, CNTs are evenly grown on the nanofibers by chemical vapor deposition. The long conductive nanofibers and CNTs are evenly introduced into the dense piezoelectric nanofiber membrane. The long conductive nanofibers serve as vertical conductive paths in the nanofiber membrane, and the CNTs serve as horizontal conductive paths in the nanofiber membrane. The two work synergistically to jointly construct a well-distributed 3D conductive network between the piezoelectric nanofibers by the synergistic action of the conductive nanofibers and CNTs, which solves the problem of difficulty in constructing conductive paths in regularly arranged and dense piezoelectric nanofiber membranes, increases the charge density, and ultimately improves the output performance of the PENG.
[0008] (2) The 3D conductive network established by the present invention can transfer the charges generated by the piezoelectric nanofibers inside the matrix to the surface area of the material, thereby inducing more induced charges on the electrodes to enhance the transmission of piezoelectric charges in the nanofibers, thereby obtaining a high-performance flexible PENG.
[0009] (3) The composite film prepared by the present invention has broad application prospects in the field of piezoelectric nanogenerators, and the improvement of its electrical properties also improves its practicality in electronic textiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a process flow chart of Example 1 of the present invention; Figure 2 This is a SEM image of nanofibers in the membrane (i.e., CNT@piezoelectric / conductive nanofiber membrane) of step 2 of Example 1 of the present invention; Figure 3 This is a SEM image of nanofibers in the membrane of step 2 of Example 2 of the present invention; Figure 4 This is a SEM image of nanofibers in the membrane of step 2 of Example 3 of the present invention; Figure 5 This is a SEM image of nanofibers in the membrane of step 2 of Example 4 of the present invention; Figure 6 This is a SEM image of nanofibers in the membrane of step 2 of Example 5 of the present invention; Figure 7 This is a SEM image of nanofibers in the membrane (i.e., piezoelectric / conductive nanofiber membrane) of step 2 of Comparative Example 1 of the present invention; Figure 8 TG test result diagram of the membranes of step 2 of Examples 1-5 of the present invention and Comparative Example 1; Fig. 9 The XRD result diagram of the film in step 2 of Example 1, Example 3, Example 5 and Comparative Example 1 of the present invention; Fig.10 The test result diagram of the dielectric constant of the film of Examples 1-5 of the present invention and step 2 of Comparative Example 1 as a function of frequency; Fig.11 The test result diagram of the dielectric loss of the films of Examples 1-5 of the present invention and step 2 of Comparative Example 1 as a function of frequency; Fig.12 The test result diagram of the conductivity of the membranes of Examples 1-5 of the present invention and step 2 of Comparative Example 1 as a function of frequency; Fig.13 The dielectric constant, dielectric loss and conductivity test results of the composite film of Example 3 of the present invention are shown in FIG. Fig.14 Graph showing the piezoelectric performance voltage test results of the PENGs of Examples 1-5 of the present invention and Comparative Example 1; Fig.15 Graph showing the piezoelectric performance current test results of the PENGs of Examples 1-5 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0011] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the present invention.
[0012] The present invention provides a method for preparing a piezoelectric nanofiber flexible composite film with a 3D conductive network (hereinafter referred to as the method), characterized in that the method comprises the following steps: (1) Preparation of piezoelectric / conductive nanofiber membrane: preparing a piezoelectric material precursor electrospinning solution and a conductive material precursor electrospinning solution, and then using the two spinning solutions as raw materials, placing them in two syringes of an electrospinning device for electrospinning to form a piezoelectric / conductive precursor nanofiber membrane; wherein all the precursor nanofibers in the piezoelectric / conductive precursor nanofiber membrane are arranged along the rotation direction of a collecting device of the electrospinning device; and then calcining the piezoelectric / conductive precursor nanofiber membrane at a high temperature to decompose the polymer carrier in the membrane to obtain a piezoelectric / conductive nanofiber membrane; Preferably, in step (1), the piezoelectric material in the piezoelectric material precursor electrospinning solution refers to a material that can be used to prepare piezoelectric nanofibers by sol-gel method, electrospinning and calcination, specifically a perovskite piezoelectric material or a piezoelectric semiconductor material; the perovskite piezoelectric material is barium titanate (BaTiO3), barium zirconate titanate-barium calcium titanate (BZT-BCT), barium calcium zirconate titanate (BCZT), barium strontium titanate (BST), bismuth titanate (BIT), sodium bismuth titanate (BNT), lead titanate (PT), lead strontium titanate (PST), lead zirconate titanate (PZT), lead lanthanum zirconate titanate (PLZT), lead magnesium niobate (PMN) or potassium sodium niobate (KNN); the piezoelectric semiconductor material is zinc oxide (ZnO); The conductive material in the conductive material precursor electrospinning solution refers to a material that can be used to prepare conductive nanofibers by a sol-gel method, electrospinning and calcination, specifically antimony tin oxide (ATO), fluorine tin oxide (FTO), fluorine antimony tin oxide (FATO), indium tin oxide (ITO) or aluminum zinc oxide (AZO).
[0013] Preferably, in step (1), the piezoelectric material in the piezoelectric material precursor electrospinning solution is barium titanate, and the precursor electrospinning solution is prepared as follows: barium acetate and tetrabutyl titanate are dissolved in a mixture of glacial acetic acid and acetylacetone under stirring at room temperature, and then PVP (polyvinyl pyrrolidone) serving as a polymer carrier in the electrospinning process is added, and after mixing evenly, a uniform BaTiO3 precursor electrospinning solution is prepared; The mass ratio of barium acetate to tetrabutyl titanate is (1~3):1, and the volume ratio of glacial acetic acid to acetylacetone is (2~5):1; the mass fraction of barium acetate in the BaTiO3 precursor electrospinning solution is 10~20wt%; the mass fraction of PVP in the BaTiO3 precursor electrospinning solution is 2~12wt%; and the molecular weight of PVP is 300,000~1.3 million.
[0014] Preferably, in step (1), the conductive material in the piezoelectric material precursor electrospinning solution is antimony tin oxide, and the precursor electrospinning solution is prepared as follows: dissolving tin chloride pentahydrate and antimony trichloride in a mixed solution of anhydrous ethanol and DMF (N,N-dimethylformamide) under stirring at room temperature, then adding PVP which acts as a polymer carrier in the electrospinning process, and mixing well to prepare a uniform ATO precursor electrospinning solution; The mass ratio of tin chloride pentahydrate to antimony trichloride is (8~16):1, and the volume ratio of anhydrous ethanol to DMF is 1:(1~4); the mass fraction of tin chloride pentahydrate in the ATO precursor electrospinning solution is 6~15wt%; the mass fraction of PVP in the ATO precursor electrospinning solution is 6~18wt%; and the molecular weight of PVP is 300,000~1.3 million.
[0015] Preferably, in step (1), the electrospinning process is as follows: the spinning needles of two syringes are placed side by side and reciprocate along the axial direction of the collecting device during the spinning process; the ratio of the precursor piezoelectric nanofibers and the precursor conductive nanofibers is controlled by the extrusion rate of the syringe on the precursor electrospinning liquid, the extrusion rate of the piezoelectric material precursor electrospinning liquid is 0.5~2.5ml / h, and the extrusion rate of the conductive material precursor electrospinning liquid is 0.2~2ml / h; the electric field strength is 15~40kV; the distance from the needle tip to the collecting device is 12~25cm; the rotation speed of the collecting device is 1000~4000r / min, so that the precursor nanofibers are arranged along the rotation direction; the air humidity is 10~60%, and the temperature is 20~40℃.
[0016] Preferably, in step (1), the calcination temperature is 400-1200° C., the heating rate is 0.5-8° C. / min, the holding time is 1-5 h, and the calcination environment is air atmosphere.
[0017] (2) Preparation of CNT@piezoelectric / conductive nanofiber membrane: CNT (carbon nanotube) is in situ grown on the piezoelectric / conductive nanofiber membrane by chemical vapor deposition (CVD) to obtain CNT@piezoelectric / conductive nanofiber membrane; Preferably, step (2) specifically comprises: immersing the piezoelectric / conductive nanofiber membrane in a cobalt nitrate solution, and allowing the solution to stand so that all the cobalt nitrate adheres to the inside and surface of the nanofiber membrane; then taking out the product, and drying to remove the solvent in the cobalt nitrate solution on the surface of the nanofiber membrane; then calcining the dried product and a carbon source at a high temperature in a H2 / Ar mixed gas to obtain a CNT@piezoelectric / conductive nanofiber membrane; Preferably, in step (2), the mass ratio of the solute in the cobalt nitrate solution to the piezoelectric / conductive nanofiber membrane is (1-20):10; Preferably, in step (2), the cobalt nitrate solution is prepared by dissolving solid cobalt nitrate particles in anhydrous ethanol, wherein the amount of anhydrous ethanol is sufficient to dissolve the solid cobalt nitrate particles.
[0018] Preferably, in step (2), the standing process is: standing at room temperature and pressure for 1 to 10 minutes.
[0019] Preferably, in step (2), the drying temperature is 40-70° C. and the drying time is 5-20 min.
[0020] Preferably, in step (2), the mass ratio of the carbon source to the piezoelectric / conductive nanofiber membrane is 1:(1-10).
[0021] Preferably, in step (2), the carbon source is xylene.
[0022] Preferably, in step (2), the flow rate of the H2 / Ar mixed gas is 200-300 sccm.
[0023] Preferably, in step (2), the volume content of H2 in the mixed gas is 5-20%.
[0024] Preferably, in step (2), the calcination temperature is 400-1000° C., the pressure is normal pressure, the heating rate is 0.5-8° C. / min, and the holding time is 1-5 h.
[0025] (3) Preparation of CNT@piezoelectric / conductive nanofiber / PDMS composite membrane: Several CNT@piezoelectric / conductive nanofiber membranes are stacked layer by layer to form a three-dimensional structure, and the arrangement direction of the nanofibers in each layer of CNT@piezoelectric / conductive nanofiber membrane is the same; then they are immersed in a PDMS solution and allowed to stand, so that the PDMS adheres to the inside and surface of the nanofiber membrane; then a curing treatment is performed to solidify the PDMS, and then the three-dimensional structure is cut along the radial direction of the nanofibers in the three-dimensional structure to obtain a CNT@piezoelectric / conductive nanofiber / PDMS composite membrane.
[0026] Preferably, in step (3), the mass fraction of the PDMS solution is 40-95wt%.
[0027] Preferably, in step (3), the standing process is: standing at room temperature and pressure for 1 to 8 hours.
[0028] Preferably, in step (3), the curing temperature is 40-120° C. and the curing time is 2-10 hours.
[0029] Preferably, the CNT@piezoelectric / conductive nanofiber / PDMS composite membrane is used as a raw material, two copper foils are adhered as electrodes to the top and bottom of the CNT@piezoelectric / conductive nanofiber / PDMS composite membrane, and wires are led out from the two electrodes to prepare a flexible piezoelectric nanogenerator.
[0030] Embodiment 1: (1) Preparation of BaTiO3 / ATO nanofiber membrane: First, prepare BaTiO3 and ATO precursor electrospinning solutions, specifically: dissolve 2.55g of barium acetate and 3.4g of tetrabutyl titanate in 6g of glacial acetic acid and 2g of acetylacetone, mix them evenly under magnetic stirring, then add 1g of PVP, stir them thoroughly to make a uniform BaTiO3 precursor electrospinning solution; dissolve 1.7268g of tin chloride pentahydrate and 0.1274g of antimony trichloride in 4.31g of anhydrous ethanol and 10.34g of DMF, then add 2g of PVP, stir them thoroughly to make a uniform ATO precursor electrospinning solution; BaTiO3 precursor electrospinning solution and ATO precursor electrospinning solution were used as raw materials, and they were placed in two syringes for electrospinning to form BaTiO3 / ATO precursor nanofiber membranes. The BaTiO3 / ATO precursor nanofiber membranes were then heated to 1000°C at a heating rate of 2°C / min and calcined for 1h to decompose PVP in the membranes, thereby obtaining BaTiO3 / ATO nanofiber membranes. The electrospinning process conditions are as follows: the spinning needles used by the two syringes are arranged in parallel and reciprocate along the axial direction of the collecting device during the spinning process; the extrusion rate of the BaTiO3 spinning solution is 1 ml / h, and the extrusion rate of the ATO spinning solution is 0.4 ml / h, so the content of the ATO precursor nanofibers in the BaTiO3 / ATO nanofiber membrane is controlled to be 12wt%; the electric field strength is 35 kV; the distance from the needle tip to the collecting device is 18 cm; the collecting device rotates at a speed of 2500 r / min; the air humidity is 25% and the temperature is 20°C; (2) Preparation of CNT@BaTiO3 / ATO nanofiber membrane: CNT was grown in situ on BaTiO3 / ATO nanofiber membrane by CVD method. Specifically, the BaTiO3 / ATO nanofiber membrane was immersed in cobalt nitrate solution and allowed to stand for 2 min to allow the cobalt nitrate to fully penetrate into the nanofiber membrane until the cobalt nitrate solution was completely absorbed. The product was then taken out and dried at 60°C for 5 min. The dried product and xylene (the mass ratio of xylene to BaTiO3 / ATO nanofiber membrane was 1:1) were placed in a tubular furnace, and a H2 / Ar mixed gas (the volume ratio of H2 to Ar was 1:9) was introduced. The temperature was then raised to 800°C at a heating rate of 3°C / min and calcined for 1 h to obtain CNT@BaTiO3 / ATO nanofiber membrane. The cobalt nitrate solution is prepared by dissolving cobalt nitrate solid particles in anhydrous ethanol, wherein the mass ratio of cobalt nitrate solid particles to BaTiO3 / ATO nanofiber membrane is 3:10.
[0031] (3) Preparation of CNT@BaTiO3 / ATO / PDMS composite membrane: Several CNT@BaTiO3 / ATO nanofiber membranes were stacked layer by layer to form a three-dimensional structure, and the arrangement direction of the nanofibers in each layer of CNT@BaTiO3 / ATO nanofiber membrane was the same; then they were immersed in a PDMS solution with a concentration of 80 wt% and allowed to stand for 2 h to allow the PDMS to adhere to the inside and surface of the nanofiber membrane; then they were cured at 60 °C for 4 h to solidify the PDMS, and then the three-dimensional structure was cut along the radial direction of the nanofibers in the three-dimensional structure to obtain a CNT@BaTiO3 / ATO / PDMS composite membrane.
[0032] Application: Two copper foils were adhered as electrodes to the top and bottom of the CNT@BaTiO3 / ATO / PDMS composite film to prepare a flexible piezoelectric nanogenerator.
[0033] Depend on Figure 1 It can be seen that a 3D conductive network consisting of ATO nanofibers as vertical conductive paths and CNTs as horizontal interconnects was successfully constructed in the CNT@BaTiO3 / ATO nanofiber membrane.
[0034] Embodiment 2: This embodiment is the same as embodiment 1, except that in step (2), the mass ratio of cobalt nitrate solid particles to BaTiO3 / ATO nanofiber membrane is 1:2.
[0035] Embodiment 3: This embodiment is the same as embodiment 1, except that in step (2), the mass ratio of cobalt nitrate solid particles to BaTiO3 / ATO nanofiber membrane is 7:10.
[0036] The PENG prepared in this example exhibits the best piezoelectric performance.
[0037] Embodiment 4: This embodiment is the same as embodiment 1, except that in step (2), the mass ratio of cobalt nitrate solid particles to BaTiO3 / ATO nanofiber membrane is 9:10.
[0038] Embodiment 5: This embodiment is the same as embodiment 1, except that in step (2), the mass ratio of cobalt nitrate solid particles to BaTiO3 / ATO nanofiber membrane is 11:10.
[0039] Comparative Example 1: This comparative example is the same as Example 1, except that in step (2), the mass ratio of cobalt nitrate solid particles to BaTiO3 / ATO nanofiber membrane is 0:1, that is, no cobalt nitrate is used.
[0040] Depend on Figure 2-7 It can be seen that as the content of cobalt nitrate in the catalyst increases, the density of the generated CNTs also increases. Figure 2 and Figure 3 As shown, a few sparse CNTs grow on the CNT@BaTiO3 / ATO nanofibers prepared in Example 1 and Example 2; when the content of cobalt nitrate catalyst increases, as shown in Figure 4 and Figure 5 As shown, the CNTs grown on the CNT@BaTiO3 / ATO nanofibers prepared in Examples 3 and 4 can already be connected between the fibers; Figure 6 As shown, the surface of the CNT@BaTiO3 / ATO nanofibers prepared in Example 5 is already covered with CNTs; Figure 7 As shown, no CNTs were found on the surface of the BaTiO3 / ATO nanofibers prepared in Comparative Example 1, which also shows that when the catalyst cobalt nitrate is not added, the difference between the fibers and the fibers not participating in the CVD reaction is not much.
[0041] Depend on Figure 8 It can be seen that through TG testing, because the BaTiO3 / ATO nanofiber membrane is stable at 800°C, and CNT thermally decomposes under high temperature conditions, it can be determined that the contents of CNT in the CNT@BaTiO3 / ATO nanofiber membrane in Examples 1-5 are 4wt%, 8wt%, 14wt%, 16wt%, and 19wt%, respectively. There is no CNT in Comparative Example 1, and the content is 0wt%.
[0042] Depend on Fig. 9 It can be seen that the XRD pattern of BaTiO3 nanofibers matches well with the standard JCPDS card #05-0626, and the peaks at 22.16, 31.56, 38.92, 45.34, 50.97 and 56.23 correspond to the crystal planes of BaTiO3 respectively. In addition, it can be seen that a splitting peak is presented near 45 °, which means that the BaTiO3 nanofibers are tetragonal crystallization. The XRD pattern of ATO nanofibers matches well with the standard JCPDS card #41-1445 of SnO2, and the peaks at 26.67, 33.89, 38.11 and 51.92 correspond to the crystal planes of ATO respectively. For the BaTiO3 / ATO nanofiber film of comparative example 1, it is observed that their respective diffraction peaks appear simultaneously and are superimposed without interfering with each other. For CNT@BaTiO3 / ATO nanofiber membrane, it was observed that its peaks all corresponded to the diffraction peaks of BaTiO3 / ATO nanofibers, and there was no problem of missing peaks, which confirmed that the crystal form did not change after the in-situ growth of CNT by CVD reaction. Fig. 9 It can be seen that with the increase of CNT content, the peak value gradually decreases.
[0043] Depend on Fig.10 It can be seen that the dielectric constant of the nanofiber membrane increases with the increase of CNT content, which can be explained by the principle of microcapacitance. The uniformly distributed conductive CNT filler can form a large number of microcapacitors, and their number increases with the increase of CNT content. As the CNT content increases, the isolation distance between CNTs decreases, which increases the average capacitance of the microcapacitors.
[0044] Depend on Fig.11 It can be seen that the dielectric loss of the nanofibrous membrane increases with the increase of CNT content, which is due to the increased current leakage due to the high conductivity of CNTs.
[0045] Depend on Fig.12 It can be seen that as the CNT content increases, the resistance decreases and the conductivity increases accordingly.
[0046] Depend on Fig.13 It can be seen that the dielectric constant, dielectric loss and conductivity of the PDMS composite with BaTiO3 / ATO hybrid nanofibers and 14wt% CNT are 368, 1.25 and 6.81×10 -11 S / m, demonstrating the insulating effect of PDMS encapsulation on the dielectric behavior.
[0047] Fig.14 and Fig.15 The voltage (Voc) and current (Isc) of PENGs under repeated release cycles at 30 kPa pressure and 2 Hz frequency are shown in Figure 2 . Fig.14 and Fig.15 It can be seen that the PENG without CNTs exhibits an output of 31V and 9.6μA (corresponding to Comparative Example 1). After the introduction of CNTs in PENG, the CNTs and ATO nanofibers work synergistically and the electrical output is significantly improved. With the increase of CNT content, Voc and Isc gradually increase. When the CNT content is 14wt%, Voc and Isc reach 64.5V and 29.6μA (corresponding to Example 3), respectively, which are 2.08 times and 3.08 times the output performance of pure BaTiO3 / ATO-based PENG, respectively. However, when the CNT content is further increased, Voc and Isc are found to show a downward trend, which is attributed to current leakage. The test results prove that the doping of CNTs improves the transfer ability of piezoelectric charges, thereby improving the output performance of PENG.
[0048] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for preparing a piezoelectric nanofiber flexible composite film with a 3D conductive network, characterized in that: The method comprises the following steps: (1) Preparation of piezoelectric / conductive nanofiber membrane: preparing a piezoelectric material precursor electrospinning solution and a conductive material precursor electrospinning solution, and then using the two spinning solutions as raw materials, placing them in two syringes of an electrospinning device for electrospinning to form a piezoelectric / conductive precursor nanofiber membrane; wherein all the precursor nanofibers in the piezoelectric / conductive precursor nanofiber membrane are arranged along the rotation direction of a collecting device of the electrospinning device; and then calcining the piezoelectric / conductive precursor nanofiber membrane to decompose the polymer carrier in the membrane to obtain a piezoelectric / conductive nanofiber membrane; (2) Preparation of CNT@piezoelectric / conductive nanofiber membrane: CNTs are grown in situ on the piezoelectric / conductive nanofiber membrane by chemical vapor deposition to obtain CNT@piezoelectric / conductive nanofiber membrane; (3) Preparation of CNT@piezoelectric / conductive nanofiber / PDMS composite membrane: Several CNT@piezoelectric / conductive nanofiber membranes are stacked layer by layer to form a three-dimensional structure, and the arrangement direction of the nanofibers in each layer of CNT@piezoelectric / conductive nanofiber membrane is the same; then they are immersed in a PDMS solution and allowed to stand, so that the PDMS adheres to the inside and surface of the nanofiber membrane; then a curing treatment is performed to solidify the PDMS, and then the three-dimensional structure is cut along the radial direction of the nanofibers in the three-dimensional structure to obtain a CNT@piezoelectric / conductive nanofiber / PDMS composite membrane.
2. The method for preparing a piezoelectric nanofiber flexible composite film having a 3D conductive network according to claim 1, characterized in that: In step (1), the piezoelectric material in the piezoelectric material precursor electrospinning solution is a perovskite piezoelectric material or a piezoelectric semiconductor material; the perovskite piezoelectric material is barium titanate, barium zirconate titanate-barium calcium titanate, barium calcium zirconate titanate, barium strontium titanate, bismuth titanate, sodium bismuth titanate, lead titanate, strontium lead titanate, lead zirconate titanate, lead lanthanum zirconate titanate, lead magnesium niobate or potassium sodium niobate; the piezoelectric semiconductor material is zinc oxide; The conductive material in the conductive material precursor electrospinning solution is antimony tin oxide, tin fluoride oxide, antimony tin fluoride oxide, indium tin oxide or zinc aluminum oxide.
3. The method for preparing a piezoelectric nanofiber flexible composite film having a 3D conductive network according to claim 1 or 2, characterized in that: In step (1), the piezoelectric material in the piezoelectric material precursor electrospinning solution is barium titanate, and the precursor electrospinning solution is prepared as follows: barium acetate and tetrabutyl titanate are dissolved in a mixture of glacial acetic acid and acetylacetone under stirring at room temperature, and then a polymer carrier PVP is added and mixed to prepare a uniform BaTiO3 precursor electrospinning solution; The mass ratio of barium acetate to tetrabutyl titanate is (1~3):1, and the volume ratio of glacial acetic acid to acetylacetone is (2~5):1; the mass fraction of barium acetate in the BaTiO3 precursor electrospinning solution is 10~20wt%; the mass fraction of PVP in the BaTiO3 precursor electrospinning solution is 2~12wt%; and the molecular weight of PVP is 300,000~1.3 million.
4. The method for preparing a piezoelectric nanofiber flexible composite film having a 3D conductive network according to claim 1 or 2, characterized in that: In step (1), the conductive material in the piezoelectric material precursor electrospinning solution is antimony tin oxide, and the precursor electrospinning solution is prepared as follows: tin chloride pentahydrate and antimony trichloride are dissolved in a mixture of anhydrous ethanol and DMF under stirring at room temperature, and then a polymer carrier PVP is added and mixed uniformly to prepare a uniform ATO precursor electrospinning solution; The mass ratio of tin chloride pentahydrate to antimony trichloride is (8~16):1, and the volume ratio of anhydrous ethanol to DMF is 1:(1~4); the mass fraction of tin chloride pentahydrate in the ATO precursor electrospinning solution is 6~15wt%; the mass fraction of PVP in the ATO precursor electrospinning solution is 6~18wt%; the molecular weight range of PVP is 300,000~1.3 million.
5. The method for preparing a piezoelectric nanofiber flexible composite film with a 3D conductive network according to claim 1, characterized in that: In step (1), the electrospinning process is as follows: the spinning needles of the two syringes are placed side by side and reciprocate along the axial direction of the collecting device during the spinning process; the extrusion rate of the electrospinning liquid of the piezoelectric material precursor is 0.5~2.5ml / h, and the extrusion rate of the electrospinning liquid of the conductive material precursor is 0.2~2ml / h; the electric field strength is 15~40kV; the distance from the needle tip to the collecting device is 12~25cm; the rotation speed of the collecting device is 1000~4000r / min; the air humidity is 10~60%, and the temperature is 20~40℃; In step (1), the calcination temperature is 400-1200°C, the heating rate is 0.5-8°C / min, the holding time is 1-5h, and the calcination environment is air atmosphere.
6. The method for preparing a piezoelectric nanofiber flexible composite film with a 3D conductive network according to claim 1, characterized in that: Step (2) specifically comprises: immersing the piezoelectric / conductive nanofiber membrane in a cobalt nitrate solution, and allowing the solution to stand so that all the cobalt nitrate adheres to the inside and surface of the nanofiber membrane; then taking out the product, and drying to remove the solvent in the cobalt nitrate solution on the surface of the nanofiber membrane; and then calcining the dried product and the carbon source in a H2 / Ar mixed gas to obtain a CNT@piezoelectric / conductive nanofiber membrane.
7. The method for preparing a piezoelectric nanofiber flexible composite film having a 3D conductive network according to claim 6, characterized in that: In step (2), the mass ratio of the solute in the cobalt nitrate solution to the piezoelectric / conductive nanofiber membrane is (1-20):10; In step (2), the standing process is: standing at room temperature and pressure for 1 to 10 minutes; In step (2), the drying temperature is 40-70°C and the drying time is 5-20 minutes.
8. The method for preparing a piezoelectric nanofiber flexible composite film with a 3D conductive network according to claim 6, characterized in that: In step (2), the mass ratio of the carbon source to the piezoelectric / conductive nanofiber membrane is 1:(1-10); In step (2), the flow rate of the H2 / Ar mixed gas is 200-300 sccm; In step (2), the volume content of H2 in the mixed gas is 5-20%; In step (2), the calcination temperature is 400-1000°C, the pressure is normal pressure, the heating rate is 0.5-8°C / min, and the holding time is 1-5h.
9. The method for preparing a piezoelectric nanofiber flexible composite film with a 3D conductive network according to claim 6, characterized in that: In step (2), the carbon source is xylene.
10. The method for preparing a piezoelectric nanofiber flexible composite film with a 3D conductive network according to claim 1, characterized in that: In step (3), the mass fraction of the PDMS solution is 40-95wt%; In step (3), the standing process is: standing at room temperature and pressure for 1 to 8 hours; In step (3), the curing temperature is 40-120° C. and the curing time is 2-10 hours.
Citation Information
Patent Citations
Preparation methods of nanometer piezoelectric film and nanometer composite piezoelectric generator
CN104201280A
Preparation method of flexible barium titanate ceramic nanofiber membrane
CN110512354A
Preparation method of self-powered adhesive bandage with stripe structure
CN115387029A
CNT-PZT nanoparticle composite, piezoelectric elememt using the same and manufacturing method thereof
KR1020160005958A
Piezoelectronic device and method of fabricating the same
US20110187240A1
Cited By
Signal amplification device and preparation method thereof
CN122248959A